Handbook of chemical regulations : benchmarking, implementation, and engineering concepts - Boss, Martha J.; Boss, Brad; Boss, Cybil; Day, Dennis W. (CRC Press, 2015)
The first book of its kind, Handbook of Chemical Regulations: Benchmarking, Implementation, and Engineering Concepts introduces the concept of global harmonization and interlinks between regulations and examines the reasons behind major requirements for chemical manufacture, article production, and distribution, importation, and usage. A compendium of environmental, health and safety, and engineering concepts for global harmonization, the book provides a road map between regulations from the European Union, the United States, and other countries who adopt similar regulations. As with any road m.